The role of organic carbon and arsenic in the formation of sediment-hosted gold deposits: A case study of the Shahuindo and Algamarca epithermal deposits, Peru - Galdos Postigo, Renzo Andres (2024)
The goal of this study is to determine the source of gold and the role played by organic carbon and arsenic in the formation of sediment-hosted gold deposits. The effect of and link between these two ubiquitous ingredients yet remains unresolved, even though most mineable gold in the Earth’s crust is hosted by this type of deposits. In this work, we tackled these fundamental questions in a case study of the Shahuindo and Algamarca deposits in the Marañon Fold and Thrust Belt of the Peruvian Andes. These deposits are representative of sediment-hosted deposits in which gold mineralization is closely associated with both carbonaceous material and arsenian pyrite. We combined a range of complementary approaches including regional-scale basin analysis, mineralogical, geochemical, and fluid-inclusion studies, coupled with modeling of fluidrock interactions. Our results show that both Shahuindo and Algamarca deposits are located in an imbricated system of four thrust-related anticlines. The mineralization, which is predominantly present in the form of invisible gold in arsenian pyrite, is hosted by sandstone reservoirs of the Cretaceous Chimú, Carhuaz and Farrat formations of an overmature petroleum system. The intersection of thrust structures with transverse strike-slip faults controlled the location of the gold mineralization. Analyses of quartzhosted fluid inclusions for homogenization temperature, salinity and element concentration patterns collectively point to a magmatic origin of the mineralizing fluid(s). In addition, our fluid-inclusion data reveal intensive interactions between the fluid and organic carbon within the sedimentary basin, leading to large concentrations of CO2 CH4 and H2S in the fluid. These reactions result in an enhancement of Au solubility in the form of AuI hydrosulfide complexes, due to the increase in H2S and pH in the fluid. These key chemical changes in the fluid upon its reaction with organic matter promoted the transport of gold through the fold and thrust belt, followed by the gold-bearing fluid accumulation in structural traps such as anticlines, and subsequent gold intake by arsenian pyrite. The ensemble of the results obtained in this work allowed us to propose a novel genetic model of formation for Shahuindo and Algamarca deposits. The model integrates the positive combined effect role of organic carbon and arsenic in the transport and concentration of gold, coupled with a favorable structural architecture of the fold and thrust belt. Furthermore, our data point to a concealed porphyry-style mineralization that may be present beneath the basin hosting the Shahuindo and Algamarca epithermal deposits. The results of this work contribute to the improvement of exploration strategies for sediment-hosted gold deposits in Northern Peru and worldwide.